The invasion of Pagurus longicarpus Say, 1817 in the Wadden Sea: Ecological niche modeling to predict its further expansion to the North and Baltic Sea - Cirillo, Leonardo [UNESP]; Rodrigues, Gabriel F. B. [UNESP]; da Silva, Alexandre R. (Springer Nature, 2025)
With the intensification of globalization in the past few decades, an increasing number of species are being established outside their natural range. An invasive species is often linked to negative impacts on native fauna, causing harmful effects on native ecosystems and resulting in financial losses. Recently the long-clawed hermit crab (Pagurus longicarpus) was introduced to the Wadden Sea, being able to compete with native species. Understanding potential distribution areas of new invasive species is crucial for predicting impacts on native fauna and facilitating effective management actions. Therefore, we assessed the environment suitability of long-clawed hermit crab to identify potential invasion areas to the North and Baltic Sea using Ecological Niche Modeling (ENM). Additionally, we investigated potential competition with native hermit crab species Pagurus bernhardus and Diogenes pugilator. Our results reveal a high environmental suitability of long-clawed hermit crab to the Wadden, North and Baltic Sea, indicating a possible expansion to new regions. Mean Primary Productivity, Mean Salinity and Mean Temperature were the main variables limiting the invasive species distribution. Furthermore, long-clawed hermit crab exhibited a great niche overlap with both native hermit crab species, presenting a wider distribution than P. bernhardus and D. pugilator, and may present as a strong competitor for native hermit crabs at the regions. The outcomes of our study provide important implications for the management and monitoring of the long-clawed hermit crab in the region, giving valuable insights for addressing potential ecological impacts.
Keywords: Biological invasion; Distribution; Environmental suitability; Long-clawed hermit crab; Niche overlap